Students' Concepts about Meteorite Impacts on Earth–Geographical Assessment and Pedagogical Consequences - Martin Müller (Zeitschrift für Geographiedidaktik, 2007)
Meteorite impacts have been an ongoing phenomenon throughout Earth's history. In order to sample students' concepts and ideas, the topic has to be assessed from a geoscientific perspective. Not only in the past but also today asteroids and comets pose a high risk for our planet. Small meteorites occur most often and only cause local damage but can nevertheless be a danger for cities. Larger meteorites are considered a risk for coastal areas due to highly likely tsunami generation. Objects with more than 2km diameter require special supervision for they can cause a global "impact winter" and lead to a mass extinction, including humankind. Interviews with representatives of the MunichRe Group, the WBGU (scientific council of the German government) and the DKKV have also shown that meteorite impacts are dealt with as a high-risk potential and one of the most dangerous natural hazards. Further connections to geography on multiple scales and dimensions (e.g. existing craters like the Nördlinger Ries; effects of an impact on the evolution of life) lead to the examination of students' knowledge and imaginations about meteorite impacts. The model of "Didaktische Rekonstruktion" (model of educational reconstruction) was used in order to help interpreting the collected data (quantitative results from 2x25 questionnaires and qualitative results from interviews conducted at the Willibald Gymnasium in Eichstätt). It combines the scientific approach, the study of students' ideas and the practice to an iterative process. The emphasis is on sampling students' (11th grade, age 16-18) ideas about meteorite impacts. Results show that • There is high interest both in the subject in general and also in special aspects (geological processes, risk and consequences of an impact on today's ecosystems and civilization) • Students gather their knowledge about meteorite impacts mainly NOT from school lessons but from TV documentaries and cinema movies • Students are aware of the threat of meteorite impacts to humanity but are unable to connect this to their individual perspective Students' preconceptions furthermore include wrong interpretations of impact statistics and size relations and are highly different from student to student. Moreover, data shows a lack of awareness of the geological timescale. The central aspect for future studies should therefore be the educational implementation of the topic "impacts" in geographical curricula.